Analysis of pine resin potential as an additive on the physical and combustion characteristics of coconut shell bio-briquettes - Eli Marcelia Anggraeni; Sekar Wahyu Ningrum; Bambang Poerwadi; Hamzah Fansuri; Rama Oktavian (Center of Biomass & Renewable Energy (CBIORE), 2026)
Indonesia is still heavily reliant on fossil fuels; however, the growth of renewable energy sources, such as biomass, offers a promising alternative energy source. Because of its high calorific value (6,500–7,600 kcal/kg) and widespread availability, coconut shell was selected for this investigation as bio-briquette. This study aimed to analyse how the properties of coconut shell bio-briquettes were affected by the carbonization time and the concentration of pine resin added as an additive. This study investigates the production and characterization of coconut shell bio-briquettes as a sustainable solid fuel. Coconut shell charcoal was carbonized at 600°C for 120, 180, and 240 min, then ground and sieved to a particle size of –60+80 mesh. Tapioca starch (5%) was used as a binder, and pine resin, derived from Pinus merkusii, was applied externally as an ignition-enhancing additive at concentrations of 2%, 4%, 6%, 8%, and 10%. The resulting bio-briquettes were analyzed for proximate parameters (moisture, ash, volatile matter, and fixed carbon) and combustion characteristics (calorific value, ignition time, and burning rate) following SNI 01-6235-2000 standards. At a carbonisation time of 240 min and a concentration of 8% pine resin, the best results were obtained in terms of moisture content (3.87%), ash (3%), volatile matter (10.80%), fixed carbon (82.33%), calorific value (7,761.21 cal/g), ignition time (63 s), and burning rate (0.1093 g/min). These findings demonstrate that pine resin can effectively enhance ignition performance without compromising the combustion stability. Coconut shell biobriquettes with the addition of pine resin show high potential as an environmentally friendly alternative fuel because they produce a high calorific value, low moisture and ash content, and fixed carbon content that meets SNI 01-6235-2000 standards and ISO 17225 for solid biofuel. These characteristic indicate that bio-briquettes can be used as a renewable energy source to replace fossil fuels for household needs and small-scale industries.